Copper(II)-Catalyzed Enantioselective Fluorination of β-Keto Esters Using Chiral Spiro Oxazoline Ligands - Narayama, Akira; Shibatomi, Kazutaka; Soga, Yoshinori; Muto, Tsubasa; Iwasa, Seiji (Synlett, 2013)
Highly enantioselective fluorination of α-alkyl-β-keto esters was performed using a chiral Lewis acid catalyst prepared from Cu(OTf)2 and chiral spiro oxazoline ligands. The fluorination proceeded in a highly enantioselective manner both when cyclic and acyclic substrates were applied to the reaction. Fluorination of α-alkylmalonates was also performed to afford the corresponding products in good enantioselectivity.
Keywords: asymmetric catalysis; fluorination; chiral ligands; spiro compounds; Lewis acid